Effect of intra-ovarian platelet rich plasma in women with poor ovarian response - Fatemeh Davari tanha; Shohreh Salimi Setudeh; Mahbod Ebrahimi; Elham Feizabad; Zahra Khalaj Sereshki; Firoozeh Akbari Asbagh; Hamideh Pakniat; Azadeh khalili; Zahra Kaveh; Sara Saeedi (Babol University of Medical Sciences, 2023)
Background: Poor ovarian responder (POR) women, whose ovarian response to gonadotropin stimulation has decreased, are at higher risk of unsuccessful in-vitro fertilization (IVF). Therefore, this study designed to evaluate the effect of intra-ovarian platelet rich plasma (PRP) on POR women. Methods: This single-arm trial research was done on 20 POR women referred to the IVF Unit, university-based hospital, Tehran, Iran between October 2020 and September 2021. For all participants, autologous PRP was injected into each ovary by transvaginal ultrasound guidance under spinal anesthesia between days 12 and 14 of the menstrual cycle. After 12 weeks of PRP injection, embryo transfers were carried out following our routine IVF department protocol. The study outcomes were the number of mature oocytes, and pregnancy rates. Results: The average age of the participants was 41.80±1.82 yr. The average infertility duration was 9.70±1.89 yrs., with 80% primary infertility type. After PRP injection, follicle-stimulating hormone levels dropped about 1% (P=0.499), anti-Mullerian hormone levels were on average 4.5% higher (P=0.356), and estradiol levels raised by 1.2% (P=0.681). The average number of oocytes and their quality increased after PRP injection, while these changes were not significant (p-value>0.05). Chemical pregnancy was detected in 3 (15%) women and clinical pregnancy was detected only in one person. Conclusion: This study revealed that PRP injection into ovaries of POR women is safe and had a tendency to improve ovarian reserve markers and serum levels of AMH, estradiol, number and quality of oocytes.